Milestones of the history (to the 95-th anniversary of the V.V. Dokuchaev Soil Science Institute) - A. L. Ivanov; B. F. Aparin (Бюллетень Почвенного института им. В.В. Докучаева)
The article considers the logic and periods of V.V. Dokuchaev Soil Science Institute development as well as the driving forces during the mentioned periods and the most important outcomes and tasks for the near future. One can distinguish four main periods in the history of the Institute, they are: organization, sustainable development, survival, revival. Some factors like scientific and organizational structure of the Institute, its contribution to the development of theoretical and applied soil science are considered as the indicators typical of each period. Firstly, the Institute structure during the initial organization period shows the priority of fundamental soil research in the leading areas: soil physics, soil chemistry, soil genesis, biology, etc. Advanced development of theoretical research allowed scientists to promptly respond to actual needs of the developing country: search for soil resources for cultivation of technical crops, development of new territories, land reclamation and hydrotechnical construction. By the 1970s a kind of sustainable scientific and organizational structure had finally formed in the Institute. In the early 90s, the Soil Science Institute entered a critical phase of development. The second decade of the XXI century became a turning point in its fate. A new strategy in the development of scientific activities of the Institute was sorely needed. The new strategy consisted of three interrelated elements. The first one was modernization of the material and technical basis for researches; the second one was strengthening of the human resources potential through attraction of motivated young researchers; and the third one was in establishing unilateral and multilateral interactions between the partners – users of scientific knowledge. The main areas of interaction were the topical issues: food security, global climate change and their implications for the country. It has been shown that society can recognize and support the scientific research only if a constant flow of information, obtained by means of different tools and methods, is provided. The significance of soil science as a fundamental discipline in the socio-economic development of the country was confirmed by the Government Resolution (2022) on the celebration of the 100-th anniversary of the V.V. Dokuchaev Soil Science Institute. The modern noosphere paradigm in soil research poses new challenges to the science, at the forefront of which is V.V. Dokuchaev Soil Science Institute.